Neuroscience and advertising - Gibbons, Justin (Henry Stewart Talks, 2009)
A beginners' guide to the brain, The emotional brain, Phineas Gage, Emotions affect decision making, Emotional anchoring, Theory of attention, A spectrum of media experiences, The power to connect